In Search of Antifungals from the Plant World: The Potential of Saponins and Brassica Species against Verticillium dahliae Kleb. - Caterina Morcia; Isabella Piazza; Roberta Ghizzoni; Stefano Delbono; Barbara Felici; Simona Baima; Federico Scossa; Elisa Biazzi; Aldo Tava; Valeria Terzi; Franca Finocchiaro (Horticulturae, 2022)
Control methods alternative to synthetic pesticides are among the priorities for both organic and conventional farming systems. Plants are potential sources of compounds with antimicrobial properties. In this study, the antifungal potentialities of saponins derived from Medicago species and oat grains and of brassica sprouts have been explored for the control of Verticillium dahliae, a widely distributed fungal pathogen that causes vascular wilt disease on over 200 plant species. All the tested plant extracts showed antifungal properties. Such compounds, able to reduce mycelium growth and conidia formation, deserve deeper in vivo evaluation, even in combination with a delivery system.